2014
DOI: 10.1021/bc500084f
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Protein–Nanoparticle Interaction: A New Gateway to Disease Therapeutics

Abstract: Molecular identification of protein molecules surrounding nanoparticles (NPs) may provide useful information that influences NP clearance, biodistribution, and toxicity. Hence, nanoproteomics provides specific information about the environment that NPs interact with and can therefore report on the changes in protein distribution that occurs during tumorigenesis. Therefore, we hypothesized that characterization and identification of protein molecules that interact with 20 nm AuNPs from cancer and noncancer cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
76
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(82 citation statements)
references
References 56 publications
6
76
0
Order By: Relevance
“…For example, the interfacial properties of inorganic nanoparticles is changed appreciably when they enter the GIT, which impacts cellular and tissue response to the nanoparticles. 117,118 Even after cellular uptake, inorganic nanoparticles may interact with cellular and/or blood proteins, which can further modify their biological fate. 76,[119][120][121] Enzyme activity: Gastrointestinal fluids contain digestive and metabolic enzymes that may change the properties of certain types of nanoparticles.…”
Section: Food Matrix and Git Effects On Nanoparticle Characteristics mentioning
confidence: 99%
“…For example, the interfacial properties of inorganic nanoparticles is changed appreciably when they enter the GIT, which impacts cellular and tissue response to the nanoparticles. 117,118 Even after cellular uptake, inorganic nanoparticles may interact with cellular and/or blood proteins, which can further modify their biological fate. 76,[119][120][121] Enzyme activity: Gastrointestinal fluids contain digestive and metabolic enzymes that may change the properties of certain types of nanoparticles.…”
Section: Food Matrix and Git Effects On Nanoparticle Characteristics mentioning
confidence: 99%
“…The uptake of nanoparticles is determined by particle-protein and corona-membrane interactions, receptor-ligand binding interactions, membrane wrapping, biomolecule interaction and conformational change in the biomolecules. Recently Giri et al 29 have presented a detailed study of the composition of the protein coronas of gold nanoparticles at incubation times between 15 and 24 h. They showed that proteins adsorbed in the first 15 min have a significantly higher isoelectric point than the mean theoretical isoelectric point of all proteins present in the incubation media. 26 It was revealed that the presence of the corona ( protein layer) inhibits the formation of Aβ fibrils (which is the main cause of Alzheimer's diseases) 27 for all of the tested nanomaterials (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…AuNP and protein interaction serve as starting point to study the biological effects of Au NPs. Usually, the high abundance proteins first arrive at and adsorb on the surface of NPs, but they are eventually replaced by high-affinity proteins to form NP-protein complexes [22]. AuNPs in biological fluids may form NP-protein complexes that can be [23].…”
Section: Resultsmentioning
confidence: 99%